Relations between the theoretical conceptions of Freire and Vygotsky: A bibliographic mapping at the National Meeting of Research in Education and Sciences – ENPEC (Research, Society and Development, 2019)
With reference to the studies focused on the theories involving the theorical processes in the context of Science Education, the conceptions of Paulo Freire and Lev S. Vygotsky, individually, have contributed to the configuration of new analysis perspectives and theorization of the scientific knowledge produced and appropriated by the subjects. With this in mind, a qualitative research of the bibliographic kind of every National Meeting of Education and Science Research (Encontro Nacional de Pesquisa em Educação e Ciência – ENPEC) issue was performed, that is, the 20 years of publications in the annals of the event (1997-2017), in which was sought to identify and analyse productions that weave relations between the ideas of Freire and Vygotsky in the area of Science Education. After this analysis, a small number of productions with these relations was identified, the existing ones focused on dialogicity in which both authors support each other, as well as the importance of the social and discursive interactions for the teaching-learning process.